2008
DOI: 10.1063/1.2839576
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz air-core microstructure fiber

Abstract: A low-loss terahertz air-core microstructure fiber is demonstrated for terahertz waveguiding. Substantially low attenuation constant less than 0.01 cm −1 has been achieved and the guiding wavelength is found to be tunable by linear scaling the fiber size. The experimental results well agree with the simulation based on the finite-difference frequency-domain method, which interprets the guiding mechanism as the antiresonant reflecting waveguiding. The simulated modal pattern shows that most terahertz field is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…A number of waveguide solutions based on technologies from both microwave and optics, as reviewed in Ref [1], have been studied. Among the dielectric solutions proposed, solid-core sub-wavelength fibers [2] (so-called THz microwires [3,4]), hollow-core and solid-core microstructured fibers [5,6], and Ag/PS-coated hollow-core glass fibers [7] have the lowest loss reported in the literature. These waveguide solutions are either large in diameter (20-30 mm), which reduces the flexibility of the waveguide structure, or are only suitable for relatively narrow band applications due to limitation in photonic bandgap bandwidth or loss restrictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of waveguide solutions based on technologies from both microwave and optics, as reviewed in Ref [1], have been studied. Among the dielectric solutions proposed, solid-core sub-wavelength fibers [2] (so-called THz microwires [3,4]), hollow-core and solid-core microstructured fibers [5,6], and Ag/PS-coated hollow-core glass fibers [7] have the lowest loss reported in the literature. These waveguide solutions are either large in diameter (20-30 mm), which reduces the flexibility of the waveguide structure, or are only suitable for relatively narrow band applications due to limitation in photonic bandgap bandwidth or loss restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of state of the art in THz waveguide fabrication, THz hollow-core and solid-core microstructured fibers [5,11,12] have been fabricated by stacking teflon or high density polyethylene capillary tubes. The tubes were stacked to form a two dimensional triangular lattice and then were fused together by either using thin layers of polyethylene film or by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches to guide optical beams have been investigated so far in the farinfrared, including solid-core [6] or polymer fibers [7], photonic crystal fibers [8], metal tubes [9], and metal wires [10,11]. High absorption in most dielectrics and Ohmic losses in metals are the most important difficulties in developing efficient guided technology across the terahertz range.…”
mentioning
confidence: 99%
“…Practically in parallel, the first to proposals of porous fibers are found in [455], [456] and [457]. In all of them it is found that the main motivation is to diminish as maximum main problem in dielectric subwavelenght rods and partially also found in dielectric tubes: bends radiation.…”
Section: Dielectric (Optic) Waveguidesmentioning
confidence: 96%
“…(a) (b) Figure 2.71: Porous Fibers (PFs) at THz frequencies 2. a) PF proposed in [456] and detail of the E-field enhancement in the air core region; b) PF manufactured in [458] from an initial PE and PMMA (sacrificial) structure.…”
Section: Dielectric (Optic) Waveguidesmentioning
confidence: 99%